EMPLOYEE PERFORMANCE EVALUATION BASED ON ORGANIZATIONAL COMMITMENT, ORGANIZATIONAL CULTURE AND GIVING INCENTIVES AT POST OFFICE IN BUKITTINGGI CITY - Nia Nadilla; Desi Permata Sari; Ai Elis Karlinda; Lusiana Lusiana (Jurnal Apresiasi Ekonomi, 2023)
ABSTRACTPerformance is the behavior displayed by someone in carrying out work according to their potential, where a work target can be completed at the right time or does not exceed the time limit provided so as to produce something meaningful for the organization, the wider community, or for himself. This study aims to evaluate employee performance based on the level of organizational commitment, organizational culture, and provision of incentives at the Post Office in the city of Bukittinggi. Methods of data collection through surveys and distributing questionnaires, with a sample of 145 employee respondents. The analytical method used is multiple regression analysis. The research results obtained based on the partial test (t test) obtained: (a) partially there is a significant influence between Organizational Commitment on Employee Performance. Thus Ho is rejected Ha is accepted. (b) partially there is a significant influence between Organizational Culture on Employee Performance. Thus it is obtained that Ho is rejected Ha is accepted. (c) partially there is a significant influence between Incentives on Employee Performance. Thus it is obtained that Ho is rejected Ha is accepted. (d) simultaneously there is an influence of organizational commitment, organizational culture, and giving incentives to employee performance. The contribution of organizational commitment, organizational culture and incentives variables is 0.644 or 64.4% on employee performance while the remaining 35.6% is influenced by variables others not examined.